(untitled) (The Pakistan Development Review, 2010)
The cornerstone of fiscal federalism is to empower provinces through fiscal decentralisation, thereby reducing the friction between them. This is achieved if the distribution of resources between provinces is judicial and equitable, reducing the biases and divides amongst the provinces and leading to a stronger federation. In Pakistan, the National Finance Commission (NFC) awards are constituted to decide the share of the provinces in the federal revenues and to redistribute this share to the provinces. Over the years, there has been a gradual increase in federal shares. The federal government has also stretched itself into several matters that fall under the provincial purview (for instance roads, irrigation, culture and tourism and rural development) [Shah (1997)]. With the aimed devolution of power from the centre to the local government, it is imperative that these provincial governments have adequate finances to effectively carry out the subjects that fall under their domain. Moreover, there has been no serious shift in resource distribution amongst the provinces themselves, in spite of the disparities in economic and social development as well as varying political and security situations. This has, in turn, contributed in aggravating the differences between provinces over time, bringing into question the success of the NFC awards in fostering integration.